Periodically inundated uvalas and collapse dolines of Upper Pivka, Slovenia - Stepišnik, Uroš (Acta geographica Slovenica, 2020)
Within the area of Upper Pivka there is a number of intermittent lakes because of oscillation of water table level close to the surface i.e. shallow karst. Our survey was focused on morphogenetic interpretation of depressions hosting intermittent lakes by means of classic morphographic mapping and sediment analyses that was supported by electrical resistivity tomography. We can interpret at least two different morphogenetic types of depressions. One type are depressions which are periodically inundated uvalas positioned in-between conical hills. The second type are circular depressions within karst plain that are collapse dolines filled with extensive flood deposits up to several metres thick.
Keywords: collapse doline; electrical resistivity tomography; električna upornostna tomografija; geomorfologija; geomorphology; karstology; krasoslovje; Slovenia; Slovenija; udornice